Reciprocal regulation of pancreatic ductal adenocarcinoma growth and molecular subtype by HNF4α and SIX1/4. Issue 5 (21st August 2020) - Camolotto, Soledad A; Belova, Veronika K; Torre-Healy, Luke; Vahrenkamp, Jeffery M; Berrett, Kristofer C; Conway, Hannah; Shea, Jill; Stubben, Chris; Moffitt, Richard; Gertz, Jason; Snyder, Eric L
Abstract : Objective: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with a 5-year survival of less than 5%. Transcriptomic analysis has identified two clinically relevant molecular subtypes of PDAC: classical and basal-like. The classical subtype is characterised by a more favourable prognosis and better response to chemotherapy than the basal-like subtype. The classical subtype also expresses higher levels of lineage specifiers that regulate endodermal differentiation, including the nuclear receptor hepatocyte nuclear factor 4 α (HNF4α). The objective of this study is to evaluate the role of HNF4α, SIX4 and SIX1 in regulating the growth and molecular subtype of PDAC. Design: We manipulate the expression of HNF4α, SIX4 and SIX1 in multiple in vitro and in vivo PDAC models. We determine the consequences of manipulating these genes on PDAC growth, differentiation and molecular subtype using functional assays, gene expression analysis and cross-species comparisons with human datasets. Results: We show that HNF4α restrains tumour growth and drives tumour cells toward an epithelial identity. Gene expression analysis of murine models and human tumours shows that HNF4α activates expression of genes associated with the classical subtype. HNF4α also directly represses SIX4 and SIX1, two mesodermal/neuronal lineage specifiers expressed in the basal-like subtype. Finally, SIX4 and SIX1 drive proliferation and regulate differentiation in HNF4α-negative PDAC. Conclusion: Our data show that HNF4α regulates the growth and molecular subtype of PDAC by multiple mechanisms, including activation of the classical gene expression programme and repression of SIX4 and SIX1, which may represent novel dependencies of the basal-like subtype.